Voicing The Reality of Colonialized Women in The Novel ‘Belenggu’ By Armijn Pane - Tang, Muhammad Rapi; Ridwan, Ridwan; Junaedi, Inayah Maharezki (Tamaddun Life, 2024)
This study explores the representation of women's subjugation during the colonial period in Indonesia through Armijn Pane's novel "Belenggu." Utilizing an interdisciplinary approach that integrates literary sociology, feminist literary criticism, and postcolonial studies, this research provides a comprehensive understanding of how the novel reflects the author's critique of patriarchal societal structures and colonial impacts on indigenous women. The analysis focuses on the main character, Sukartini, highlighting her struggle for equality and autonomy. Despite being educated and progressive, Sukartini is depicted as trapped within socio-cultural and political constraints, influenced by entrenched patriarchal norms and colonial domination. This study reveals the dual layers of oppression faced by women, emphasizing the compounded struggles due to both gender and colonial subjugation. By examining Sukartini's character, the research illustrates how deeply ingrained patriarchal norms and colonial dominance restrict women's roles and voices. The findings contribute to Indonesian literary sociology by expanding the scope of analysis to include gender and postcolonial issues, underscoring the importance of examining literary works through multiple theoretical lenses. Moreover, the study highlights the role of literature in spreading awareness, providing social critique, and inspiring advocacy for gender equality and justice. "Belenggu" serves as a poignant critique of historical and ongoing gender inequality, reinforcing the relevance of literary analysis in understanding and addressing complex social issues. This research offers a nuanced perspective on the socio-political contexts shaping narratives, advocating for continued scholarly attention to literature as a means of promoting social change and a more equitable society.